PENGARUH METODE DAN LAMA PENGOLAHAN TERHADAP ANALISIS MUTU UBI JALAR ORANGE (Ipomoea batatas L) - Rima Purwanti; Ratnawaty Fadilah; Subari Yanto (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of the method and duration of processing on the analysis of the quality of orange sweet potatoes (Ipomoea batatas L). The study used a randomized block design consisting of two factors, namely the processing method and the duration of processing carried out three times. The treatments in the study were processing methods (steaming and frying) and duration of processing (5 minutes, 10 minutes, and 15 minutes) with a heating temperature of 100 ° C. Observation data were analyzed using Variety Analysis (ANOVA) then continued with Duncan Test. The results of the study showed that the interaction of the processing method variables and the duration of processing were not significantly affected. Beta-carotene, anthocyanin, fiber content, color and taste are only influenced by processing methods and duration of processing, while texture and aroma are only influenced by duration of processing . The best treatment of the method and duration of processing of orange sweet potato (I. batatas L) was by steaming method for 15 minutes with beta-carotene (0.07%), anthocyanin (8.99%), fiber content (0.93%) , color and aroma (rather like), and texture and taste (likes).